2014
DOI: 10.1071/rd13007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of bovine follicular components as markers of oocyte developmental potential

Abstract: Abstract. The follicle is a unique micro-environment within which the oocyte can develop and mature to a fertilisable gamete. The aim of this study was to investigate the ability of a panel of follicular parameters, including intrafollicular steroid and metabolomic profiles and theca, granulosa and cumulus cell candidate gene mRNA abundance, to predict the potential of bovine oocytes to develop to the blastocyst stage in vitro. Individual follicles were dissected from abattoir ovaries, carefully ruptured under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 34 publications
5
67
0
12
Order By: Relevance
“…Fertil Steril 2014. decrease in the relative expression of P450 c17 versus 3bHSD activity, causing a shift away from androgen and estrogen to P 4 production for appropriate endometrial luteinization (31,53). Follicular fluid P 4 concentrations do not appear to alter the ability of the oocyte to undergo fertilization or subsequent development (54)(55)(56).…”
Section: Oocyte Maturationmentioning
confidence: 85%
See 1 more Smart Citation
“…Fertil Steril 2014. decrease in the relative expression of P450 c17 versus 3bHSD activity, causing a shift away from androgen and estrogen to P 4 production for appropriate endometrial luteinization (31,53). Follicular fluid P 4 concentrations do not appear to alter the ability of the oocyte to undergo fertilization or subsequent development (54)(55)(56).…”
Section: Oocyte Maturationmentioning
confidence: 85%
“…Several amino acids (i.e., glutamate, glycine, and alanine) (56) and carbohydrates (i.e., glucose and lactate) also may vary in follicles containing oocytes that can or cannot undergo embryogenesis (155,156). In addition, fatty acids in follicular fluid also are important, since lower palmitic acid and total saturated fatty acid concentrations, reduced n-6:n-3 polyunsaturated fatty acid ratios, and elevated linolenic, stearic, and arachodonic acid levels are associated with good oocyte quality (56,157).…”
Section: Metabolitesmentioning
confidence: 98%
“…Khalil and Lawson [16] were first to identify Te, P4 and A4 as the major steroid hormones present in sFF. Matoba et al [31] compared distribution of steroid concentrations among the oocytes, which formed and failed to form blastocysts, and found that concentrations of Te, P4, and E2 in sFF were not predictive of the formation of blastocysts. In agreement with observations of Matoba et al, we did not find an association of P4 and E2 concentrations with the IVF outcomes; however a tendency toward a lower Te was found in the LB group.…”
Section: Discussionmentioning
confidence: 98%
“…Also, C16:0 supplemented into IVM medium negatively affected the postfertilization development [12, 13]. C16:0 was also described as a potential marker of reduced quality of immature bovine COCs [8, 31] and reduced blastocyst rate [14]. Another FA included into the multivariate model (oleic acid – C18:1cis9) exerted a positive effect on lipid accumulation, oocyte maturation and embryo development in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sinclair et al [8] observed correlation between the concentrations of palmitic and stearic fatty acids (FAs) and morphology of the bovine COC; however, no relation with blastocyst rate has been found. A recent manuscript of Matoba et al [14] described relations among FF composition (e.g., fatty acids, amino acids, steroids), mRNA relative abundance in cumulus, granulose and theca cells and blastocyst rate. It emphasized the metabolomic profile of follicular tissues as a source of information on oocyte quality.…”
mentioning
confidence: 99%